2016
DOI: 10.1080/02643294.2016.1182480
|View full text |Cite
|
Sign up to set email alerts
|

Identifying thematic roles from neural representations measured by functional magnetic resonance imaging

Abstract: The generativity and complexity of human thought stem in large part from the ability to represent relations among concepts and form propositions. The current study reveals how a given object such as rabbit is neurally encoded differently and identifiably depending on whether it is an agent ("the rabbit punches the monkey") or a patient ("the monkey punches the rabbit"). Machine-learning classifiers were trained on functional magnetic resonance imaging (fMRI) data evoked by a set of short videos that conveyed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The dog in Dog chases cat is neurally distinguishable from the dog in Cat chases dog , indicating that the neural encoding is more than just the sum of the individual concept representations. In another study using the same approach as the current one, a classifier was able to reliably discriminate Monkey pats rabbit and Rabbit pats monkey and to correctly assign thematic roles to the two animal concepts (Wang, J., Cherkassky, V. L., Just, 2016). Thus, the thematic role encoding could be part of a structured sentence representation that plays a role in determining how the components of a concept are selectively modulated.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The dog in Dog chases cat is neurally distinguishable from the dog in Cat chases dog , indicating that the neural encoding is more than just the sum of the individual concept representations. In another study using the same approach as the current one, a classifier was able to reliably discriminate Monkey pats rabbit and Rabbit pats monkey and to correctly assign thematic roles to the two animal concepts (Wang, J., Cherkassky, V. L., Just, 2016). Thus, the thematic role encoding could be part of a structured sentence representation that plays a role in determining how the components of a concept are selectively modulated.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have found distinct activation patterns associated with the neural representations of concepts of varying degrees of semantic abstractness (Anderson et al, 2014; Ghio et al, 2016; Wang et al, 2013). A few studies have further demonstrated the ability to associate brain activation patterns with inter-concept relations in a proposition (Frankland and Greene, 2015; Wang et al, 2016). However, characterizing the neural representations of sentences and the effect of contexts has remained a considerable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Greene (2015, 2020) used sentence stimuli to isolate distinct areas in left superior temporal sulcus (STS) that are sensitive to the identity of the agent vs. the patient. Wang et al (2016) found that the same (or nearby) STS regions also contained information about thematic roles in videos depicting agentpatient interactions. However, the latter study identified a number of other regions that were sensitive to thematic role information, including clusters in the right posterior middle temporal gyrus and right angular gyrus, suggesting that left STS is not the only region implicated in thematic role processing.…”
Section: Relationship To Theories Of Semantics In the Brainmentioning
confidence: 92%
“…First, the relatively uncontrolled properties of the naturalistic paradigms and the substantial differences across stimuli in both the localizer and main tasks might have been unsuitable for detecting subtler linguistic distinctions; and the definition of a single participant-specific fROI in each mask might have compromised our ability to identify distinctions among small regions that lie in close proximity to one another (e.g., Humphries et al, 2005;Hagoort, 2014;Wilson et al, 2018). Nonetheless, whether such distinctions as previously reported in the literature are replicable, and whether they reflect language-specific functions rather than more general, conceptual processes, remains debated (For one such example, see Dapretto and Bookheimer, 1999;Siegelman et al, 2019; for another, see Frankland and Greene, 2015;Wang et al, 2016;Anderson et al, 2018; see also Vigliocco et al, 2011;Moseley and Pulvermüller, 2014).…”
Section: Why Functional Dissociations Among Language Regions Might Gomentioning
confidence: 99%